Case Series: Free vascularized costochondral grafts in upper extremity reconstruction - Kamphuis, Saskia J. M.; Schaefer, Dirk J.; Kaempfen, Alexandre (Frontiers in Surgery, 2025)
IntroductionCostochondral grafting is well-known reconstructive option for the temporomandibular joint. In the upper extremity, non-vascularized costochondral grafts have been used for radial head reconstruction, for osteoarthritis of the trapeziometacarpal joint and proximal pole reconstruction of the scaphoid. Evidence suggests that vascularization of bone grafts lead to a higher union rate and a faster time to union. To avoid other donor sites and improve healing times we endeavored using vascularized costochondral grafts for skeletal reconstruction of the hand.MethodsIn this report, we present the operative technique and three cases of reconstructions. They comprise one case of a third metacarpal head defect including cartilaginous tissue due to avascular necrosis (Mauclair's or Dieterich's disease), one case of scaphoid proximal pole reconstruction due to necrosis and one case of a third metacarpal head reconstruction after direct trauma. Patients’ complaints included pain and clicking of the joint upon movement of the joint. There were also concerns about osteoarthritis and joint destruction on the future. Medium-term outcome showed good results concerning pain as well as normal range of motion without clicking of the joint.ConclusionOsseocartilaginous grafts are not readily available as a reconstructive option. Donor sites at the knee, metatarsophalangeal and the hamate risk a permanent damage and functional deficit. Furthermore, these grafts are not easily vascularized. Costochondral grafts present a viable option with a challenging dissection, but no mid- to long-term functional loss at the donor site.